'[Le] Besoin de définir' and 'le danger de s'embrouiller': Balzac's Les Employés and the physiologies. (2nd April 2016) - O'Neil-Henry, Anne
Abstract : Originally published as La Femme supérieure in 1837, the novel that would eventually become Les Employés in 1844 underwent drastic revision after the appearance of Balzac's Physiologie de l'employé in 1841. This essay uses close reading and a genetic approach to examine Balzac's understudied Les Employés and the two previous versions of this work, and argues that the novel actively stages the author's ambivalent relationship with the physiologies . While Balzac often depicts his characters in the manner of those in physiologie series and recycles typological passages from his own Physiologie into the final edition of the novel, numerous passages in Les Employés show the author's resistance to the very goals of this typological method. These generic tensions, which play out on the level of plot and style in the multiple formats of Les Employés, mirror tensions between high and low literature in the nascent literary field in which Balzac and his contemporaries published.